TRENDS IN INVESTMENT FOR THE DEVELOPMENT OF COMPETITIVE POTENTIAL IN AGRICULTURAL ENTERPRISES - IPATOV, Anatolii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is dedicated to studying the formation and development aspects of the competitive potential of agricultural enterprises in Ukraine under modern economic challenges, including global competition, climate change, financial instability, and the consequences of the full-scale invasion. It aims to analyze, systematize, and generalize the existing theoretical and methodological framework concerning the formation of competitive potential in agricultural enterprises and to investigate the trends in investing in their development. The theoretical aspects of forming an agricultural enterprise’s competitive potential are explored. A farming enterprise’s competitive potential is a combination of resources, capabilities, and competencies that ensure its ability to operate efficiently and sustainably in a competitive environment. It is determined to consist of the following components: production resources, financial capabilities, innovation potential, human resources, and management competencies. The research justifies that investments guarantee the development of the competitive potential of agricultural enterprises, as they provide the resource base for innovation, production modernization, and increased operational efficiency. The study of investment volumes in the competitive potential of agricultural enterprises shows that they actively invest in updating their technical base and developing infrastructure. However, significant problems remain regarding the uneven distribution of investments among enterprises of different sizes. It has been found that investments in intangible assets, particularly in software and patents, stay low, which indicates insufficient development of digital technologies and intellectual property in the agricultural sector and hinders the development of its competitive potential. To overcome the identified problems, a comprehensive approach to investing in agricultural enterprises’ competitive potential is emphasized. This approach should be based on implementing institutional reforms, supporting small businesses, and developing human capital and infrastructure. With stable financing, the activation of international cooperation, and efficient use of investments, agricultural enterprises will have the potential for sustainable development and strengthening Ukraine’s position.